Una discusión teórica en torno al concepto de "revolución" - Asensio Alonso, Carlos L. (Nómadas. Critical Journal of Social and Juridical Science, 2013)
Since the concept of “revolution” was coined, and especially after the controversial events lived since 2010 in the Islamic world, this notion has frequently been used to refer to every violent and traumatic episode produced on a state. To promote a more accurate use of the concept and elucidate what we really speak about when we refer to a “revolution”, we will analyze some of the political thoughts of five of the most important political scientists of the history, to systematize a minimum definition of this term and generate a necessary discussion about the legitimacy of the use of the violence in these difficult political and social situations.